Comparative Evaluation of Structured Clinical Case Examination with Traditional Long-Case Examination for Clinical Competence Assessment - Hetal Pandya (Journal of Integrated Health Sciences)
Background: The clinical examinations are of key importance in competency assessment for medical education. However, in traditional long-case examination (TLCE), the product of history taking and physical examination is assessed, and the process is not observed. We suggest a structured clinical case examination (SCCE) with the aim to develop the best possible evaluation method for clinical competencies of undergraduate medical students. Methodology: A new assessment method SCCE based on principles of (1) direct observation, (2) objectivity, and (3) structured format was developed. This cross-sectional study was done during the internal ward ending examination of 3rd-year clinical batch. Students' views about TLCE were taken. The examination with SCCE and TLCE methods was taken by four subject faculties for two subgroups A and B, respectively. Feedback was taken from students and examiners in preformed questionnaire. Faculties' views regarding feasibility, objectivity, process, content, impact on assessment, and learning were noted through focus group discussion. Results: On quantitative analysis of results of both methods, SCCE has found to have a better categorization of the students in competent, average competent, and noncompetent groups, while TLCE group has shown clustering of students (up to 66%) in the average group. Almost all students strongly agreed that SCCE method is better than traditional method on almost all parameters. All examiners found this new method feasible, doable, and more objective. Conclusions: The proposed SCCE method fulfills almost all characteristics for ideal clinical competency assessment method. It can be easily implemented as an assessment method in clinical subjects.